2013
DOI: 10.1007/s12031-013-0176-4
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterases as Biomarkers for Parasympathetic Dysfunction and Inflammation-Related Disease

Abstract: Accumulating evidence suggests parasympathetic dysfunction and elevated inflammation as underlying processes in multiple peripheral and neurological diseases. Acetylcholine, the main parasympathetic neurotransmitter and inflammation regulator, is hydrolyzed by the two closely homologous enzymes, acetylcholinesterase and butyrylcholinesterase (AChE and BChE, respectively), which are also expressed in the serum. Here, we consider the potential value of both enzymes as possible biomarkers in diseases associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 82 publications
0
38
1
3
Order By: Relevance
“…In past studies, we demonstrated the close correlation between our biomarkers and parallel physiological variables such as resting and recovery heart rate after stress testing (21,22,36).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In past studies, we demonstrated the close correlation between our biomarkers and parallel physiological variables such as resting and recovery heart rate after stress testing (21,22,36).…”
Section: Discussionmentioning
confidence: 52%
“…Activation of this "cholinergic reflex" has been shown to alleviate inflammatory disease, including endotoxemia and septic peritonitis (34). However, hyperactivation of this suppressive effect may also increase the susceptibility to subsequent infection (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…However, vagal deregulation has been associated with disruption in several measures of biopsychosocial well-being, such as positive emotions, social connectedness (Kok et al, 2013), satisfaction with life, depression, and global functioning (Kogan, Gruber, Shallcross, Jord, & Mauss, 2013). Some studies also suggest that parasympathetic deregulation may contribute to physical disorders such as hypertension due to an increase in cardiac output (Brindle et al, 2014), and a number of disorders associated with inflammatory processes (Shenhar-Tsarfaty et al, 2014). These observations suggest that ruminating about one's wrongdoing may also negatively impact emotional and physical well-being.…”
Section: The Effects Of Being Begrudgedmentioning
confidence: 99%
“…was less relevant. Therefore, seeking forgiveness as a humbly repentant process -independent from receiving forgiveness or not -could improve well-being and physical health by promoting vagal upregulation (Kogan et al, 2013;Kok et al, 2013;Shenhar-Tsarfaty et al, 2014). emotionally, valence during rumination was negative, and it became even more negative during the begrudged condition.…”
Section: The Effects Of Being Begrudgedmentioning
confidence: 99%
“…Separately, recent studies suggested the implication of cholinergic signaling in anti-inflammatory action by showing that AChE mRNA-targeting miRNA-132, which would reduce AChE mRNA expression, could attenuate the inflammation [50][51][52].…”
Section: Accepted Manuscriptmentioning
confidence: 99%